2012
DOI: 10.1002/jbm.a.34536
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of allogeneic and autologous mesenchymal stromal cells and osteoprogenitor cells in augmenting bone formation around massive bone tumor prostheses

Abstract: Spraying autologous mesenchymal stromal cells (MSCs) onto hydroxyapatite (HA)-coated ingrowth collars, located at the shoulder of massive bone tumor implants, significantly increased extracortical bone-bridging and osteointegration in an ovine model. In this study, we investigated the hypothesis that allogeneic MSCs and osteoprogenitor cells (OPCs) will augment bone growth equally when compared with autologous BMSCs. All collars were HA coated. In group i, the HA collar was coated with fibrin glue only. Cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…However, a radiolucent line between the extracortical bone and the shaft of the implant in the Noncollar Group clearly was evident in all cases except one. The importance of osteointegration at the shoulder has been recognized and some experimental studies have investigated methods to enhance extracortical bone formation, including the use of bone morphogenetic proteins [22] and stem cells [9,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, a radiolucent line between the extracortical bone and the shaft of the implant in the Noncollar Group clearly was evident in all cases except one. The importance of osteointegration at the shoulder has been recognized and some experimental studies have investigated methods to enhance extracortical bone formation, including the use of bone morphogenetic proteins [22] and stem cells [9,18].…”
Section: Discussionmentioning
confidence: 99%
“…Although most previous studies have used allogeneic MSCs due to their unique properties, some studies have reported that allogeneic MSCs induce memory T‐cell response resulting in cell rejection (Nauta et al , ). An in vivo study reported that no osteointegration was seen in allogeneic MSCs, and that an increased immunological response within soft tissue was observed, compared with autologous MSCs (Coathup et al , ). However, no T‐cell response with inflammatory markers was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Kalia et al 126 and Coathup et al 127 sprayed autologous and allogenic MSCs or differentiated MSC-derived osteoblasts in fibrin glue onto hydroxyapatite coated ingrowth collars of massive bone tumor implants and studied the integration of these implants in a sheep model. 126,127 Autologous MSCs and MSC-derived osteoblasts but not allogenic MSCs increased implant integration. Thus transplanted autologous MSCs can be utilized to enhance initial implant integration but clinical studies in humans remain to be conducted.…”
Section: Mscs For Improving Initial Implant Integrationmentioning
confidence: 99%